2013
DOI: 10.1107/s0907444912051529
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical characterization of the cytosolic wheat cyclophilin TaCypA-1

Abstract: Cyclophilins belong to a family of proteins that bind to the immunosuppressive drug cyclosporin A (CsA). Several members of this protein family catalyze the cis-trans isomerization of peptide bonds preceding prolyl residues. The present study describes the biochemical and structural characteristics of a cytosolic cyclophilin (TaCypA-1) cloned from wheat (Triticum aestivum L.). Purified TaCypA-1 expressed in Escherichia coli showed peptidyl-prolyl cis-trans isomerase activity, which was inhibited by CsA with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…3; Table I). The k cat /K m value for the wild-type CsCyp (5.6 s 21 mM 21 ) is consistent with values determined for other Cyp proteins (Dornan et al, 1999;Laxa et al, 2007;Sekhon et al, 2013). In addition, while the C40S and C168S mutants were similarly inhibited by CsA, the double mutant was more strongly inhibited by CsA relative to the wild-type protein ( Fig.…”
Section: On the Structural (Dis)similarities Between Classical And DIsupporting
confidence: 73%
See 2 more Smart Citations
“…3; Table I). The k cat /K m value for the wild-type CsCyp (5.6 s 21 mM 21 ) is consistent with values determined for other Cyp proteins (Dornan et al, 1999;Laxa et al, 2007;Sekhon et al, 2013). In addition, while the C40S and C168S mutants were similarly inhibited by CsA, the double mutant was more strongly inhibited by CsA relative to the wild-type protein ( Fig.…”
Section: On the Structural (Dis)similarities Between Classical And DIsupporting
confidence: 73%
“…Although 3D structures of divergent Cyps have been reported, the functional role of their unique structural elements (i.e. divergent loop, invariable Cys pair, and stabilizing Glu) remained unclear (Dornan et al, 1999;Taylor et al, 2001;Sekhon et al, 2013). Here, we show that, instead of coordinating a metal ion with His-54, as proposed previously (Dornan et al, 1999;Taylor et al, 2001), Cys-40 and Cys-168 form a disulfide bridge that blocks protein activity.…”
Section: Cscyp Binds Selectively To a Ctd Heptad Repeatmentioning
confidence: 55%
See 1 more Smart Citation
“…Modelling of the 3D structure of LRT2 was performed as previously described 54 through the SWISS-Model server (http://swissmodel.expasy.org) using the crystal structure of wheat TaCypA-1 (PDB ID: 4E1Q) as a template 34 . Molecular graphics were presented using PyMOL software (http://www.pymol.org/).…”
Section: Methodsmentioning
confidence: 99%
“…6a) and mutations in this residue of rice LRT2/OsCYP2 and moss PpDGT cause severely impaired auxin signalling 17,30 . Homologous structure modelling based on the crystal structure of wheat (Triticum aestivum) TaCypA-1 (PDB code: 4E1Q) 34 , a cyclophilin sharing 87% identity with LRT2, revealed that Gly 72 is located at the surface of LRT2 immediately adjacent to a b-sheet ( Supplementary Fig. 6b).…”
Section: Lrt2 Catalyses Cis/trans Isomerization Of Osiaa11 Peptidementioning
confidence: 99%